2020
DOI: 10.1016/j.infbeh.2019.101419
|View full text |Cite
|
Sign up to set email alerts
|

Infant-directed language following a brief behavioral parenting intervention: The importance of language quality

Abstract: Behavioral parenting interventions decrease early childhood behavior problems and increase positive parenting skills. However, few studies have examined the impact of low intensity interventions for infants at risk for behavior problems on changes in parent language. This study examined the effect of a brief parenting intervention, the Infant Behavior Program, on changes in parent linguistic input and its influence on infant language. Participants were 58 mothers and their12-to 15-month-olds, with elevated lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 46 publications
1
16
1
1
Order By: Relevance
“…Future researchers should consider using a simplified measurement system. Previous caregiver-infant interventions that measured caregiver behavior as the dependent variable and included multiple RC responses (e.g., labeling, praise, imitation) counted caregiver responses during fixed-length sessions (see Heymann et al, 2020). Counting imitation rather than calculating per opportunity will make measurement procedures less time-consuming and complicated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future researchers should consider using a simplified measurement system. Previous caregiver-infant interventions that measured caregiver behavior as the dependent variable and included multiple RC responses (e.g., labeling, praise, imitation) counted caregiver responses during fixed-length sessions (see Heymann et al, 2020). Counting imitation rather than calculating per opportunity will make measurement procedures less time-consuming and complicated.…”
Section: Discussionmentioning
confidence: 99%
“…Dunst et al (2008) identified critical characteristics of empirically supported caregiver training that aims to increase RC with infants: (a) teaching awareness of infant behavior as communication, (b) teaching how to interpret infant behavior (discrimination), and (c) teaching to engage in contingent responses. During RC interventions, caregivers are taught to engage in responsive, child-directed interactions that include: (a) delivering behaviorspecific praise, (b) tacting (e.g., labeling, describing) environmental objects according to the child's attention, (c) vocal imitation (reflection), (d) motor imitation, and (e) positive affect (e.g., baby-talk, expressive tone; Heymann et al, 2020;Markova & Legerstee, 2006;Roberts & Kaiser, 2011;Schreibman et al, 2015;Wainer & Ingersoll, 2015). Effective training components include information, modeling, rehearsal, and feedback (i.e., behavior skills training [BST]; (Parsons et al, 2012).…”
mentioning
confidence: 99%
“…Business as usual head start and early head start Strayhorn and Weidman ( 1989 ) Preventive mental health intervention BG Research staff Minimal intervention. Shown the first two videotapes of the experimental group and received a copy of the parent handout Tachibana et al ( 2012 ) Mother–child play activity program X CR Other Received play activity program after completion of assessment schedule Walker et al ( 2004 ) Psychosocial intervention based on the programme for the enrichment of interactions between mothers and children X X M Clinical health workers Infants were visited weekly to obtain information on infant feeding and morbidity ER emotional responsiveness, BG behavioural guidance, CR cognitive responsiveness, M mixed; combination of 2 + targets a Sample A (Clarke et al, 2012 ; Sheridan et al, 2011 ); Sample B (Jeong et al, 2019 ; Obradovic et al, 2016 ; Yousafzai et al, 2014 ; Yousafzai et al, 2016 ); Sample D (Brennan et al, 2013 ; Chang et al, 2015 ; Chang et al, 2017 ; Connell et al, 2019 ; Lunkenheimer et al, 2008 ); Sample E (Barrera et al, 1986 ; Barrera et al, 1991 ); Sample F (Green et al, 2015 ; Green et al, 2017 ); Sample G (Bagner et al, 2016 ; Garcia et al, 2019 ; Heymann et al, 2020 ); Sample H (Kaaresen et al, 2008 ; Nordhov et al, 2010 ...…”
Section: Resultsmentioning
confidence: 99%
“…Treating the family as a mechanism (Donzelot, 1977/1979, p. 94) that can be optimised, interventions range from small intervention studies (e.g. Gibbard & Smith, 2016; Heymann et al, 2020; Hindman et al, 2016; Laundry et al, 2008; McGillian et al, 2017) to large-scale application of policies (Lieberman, 2018) and programmes such as Sure Start (Potter & Hodgson, 2007) and Head Start (Lipsky, 2013). The focus of these interventions – the vast majority of which have been in the USA and Europe (Roberts et al, 2019) – is often on changing the language environment, despite a lack of evidence for what constitutes an ‘appropriate environment’ and what aspects of poverty affect language (Marshall et al, 2007, p. 552).…”
Section: The Motherhood Debate As Regime Of Truth: An Outline Account4mentioning
confidence: 99%